Konstruksi Kalimat Imperatif dalam Bahasa Karo - Isa Dora Perbina Br Karo; Ernanda Ernanda; Rengki Afria (Kajian Linguistik dan Sastra, 2023)
Abstract This study aims to describe the form of imperative sentence construction in the Batak Karo language. This research was conducted in April 2022. The type of research used is descriptive qualitative research. The data of this research are imperative sentences in the Batak Karo language. Data collection techniques using interview techniques, fishing techniques, and recording techniques. Data analysis uses data reduction, data presentation, and verification. The results of this study are the existence of smooth and rough speech in imperative sentences in the Batak Karo language. Of the 5 types of imperative sentences found construction, namely the imperative sentence prohibition found 3 constructions in the Batak Karo language, namely S-P-O, S-P, and P-O-S. In imperative sentences, there are 4 constructions, namely S-P-O, S-P-O-K, P-S-O-K, and P-S-O. The imperative sentence of invitation found 3 constructions namely S-P-O, S-P-K, S-P-O-K, and P-S-K. In imperative sentences, there are 3 constructions, namely S-P-O, S-P-O-K, and P-S-O-K. Imperative sentences usually have 2 constructions, namely S-P-O, and S-P-O-K. and found the construction of NP, VP, Rails, Particles, Determinants, Prepositions. Abstrak Penelitian ini bertujuan untuk mendeskripsikan bentuk konstruksi kalimat imperatif dalam bahasa batak karo. Penelitian ini dilakukan pada bulan April 2022. Jenis penelitian yang digunakan adalah penelitian deskriptif kualitatif. Data penelitian ini ialah kalimat imperatif dalam Bahasa batak karo. Teknik pengumpulan data menggunakan teknik wawancara, teknik pancing, serta teknik rekam. Analisis data menggunakan reduksi data, penyajian data, dan verifikasi. Hasil penelitian ini adalah adanya tuturan halus dan kasar pada kalimat imperatif dalam bahasa batak karo. Dari 5 jenis kalimat imperatif ditemukan konstruksi yaitu pada kalimat imperatif larangan ditemukan 3 konstruksi dalam bahasa batak karo yakni S-P-O, S-P, dan P-O-S. kalimat imperatif suruhan ditemukan 4 konstruksi yakni S-P-O, S-P-O-K, P-S-O-K, dan P-S-O. Kalimat imperatif ajakan ditemukan 3 konstruksi yakni S-P-O, S-P-K, S-P-O-K, dan P-S-K. Kalimat imperatif permintaan ditemukan 3 konstruksi yakni S-P-O, S-P-O-K, serta P-S-O-K. Kalimat imperatif biasa ditemukan 2 konstruksi yakni S-P-O, dan S-P-O-K. dan ditemukanÂ  konstruksi NP, VP, Rel, Partikel, Determinan, Preposisi.